Magnetic microcapsule capable of preventing particle sedimentation, preparation method of magnetic microcapsule and magnetic film

By using a mixture of anionic and cationic polymers in the wall of magnetic microcapsules and adding a suspension stabilizer to the core material to form a stable cross-linked grid structure and electrostatic adsorption layer, the problems of capsule wall damage and particle stability are solved, and the performance of the writing board is significantly improved.

CN119673606APending Publication Date: 2025-03-21深圳市鑫盛智能科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411849506.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the writing process, existing magnetic microcapsules are prone to inability to migrate effectively due to damage to the capsule wall, which affects clarity, and the stability of modified magnetic particles is low, affecting product quality.

Method used

A mixture including anionic polymer and cationic polymer is used as the wall material, and magnetic particles, non-magnetic particles, oily solvents and suspension stabilizers are added to the core material. A stable cross-linked grid structure and electrostatic adsorption layer are formed by adding suspension stabilizers to prevent particles from settling and aggregation.

Benefits of technology

It significantly improves the wall strength of the magnetic microcapsules, prevents the capsule wall from being damaged, ensures writing fluency and trace durability, and improves the blackness, contrast and stability of the magnetic film and writing board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673606A_ABST
    Figure CN119673606A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of microcapsules, provides a magnetic microcapsule capable of preventing particle sedimentation, a preparation method of the magnetic microcapsule and a magnetic film, and aims to solve the problems of low writing smoothness and poor trace durability due to particle sedimentation and aggregation in the prior art. The magnetic microcapsule comprises a wall material and a core material, the wall material is a mixture comprising an anionic polymer and a cationic polymer, and the core material is a mixture comprising magnetic particles, non-magnetic particles, an oily solvent and a suspension stabilizer; the suspension stabilizer comprises any one or more of phthalic ester, polyamide wax, polysiloxane, sorbitan oleate, sorbitan monostearate, silicon dioxide, magnesium aluminum silicate and magnesium lithium silicate; according to the invention, magnetic particles and non-magnetic particles can be prevented from settling and gathering, and writing fluency and trace durability are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention is a divisional application of the invention patent application filed on July 31, 2024, with the invention name “Magnetic microcapsules, preparation methods thereof and magnetic films” and application number 202411039100.5. Technical Field

[0002] The invention relates to the technical field of microcapsules, in particular to a magnetic microcapsule capable of preventing particle sedimentation and a preparation method thereof and a magnetic film. Background Art

[0003] With the development of technology, magnetic writing boards use microcapsule encapsulation technology to replace the traditional honeycomb structure. The size of the microcapsule is much smaller than the traditional honeycomb small chamber, which significantly improves the handwriting resolution and clarity.

[0004] Nevertheless, in practical applications, there are still problems such as insufficient contrast, blackness, and stability. In response to these challenges, a patent application document with application publication number CN117732384 proposes a magnetic microcapsule and a preparation method thereof. The shell material of the magnetic microcapsule in the application document is the reaction product of gelatin and anionic polymers, and the core material is a suspended mixture of modified non-magnetic particles, modified magnetic particle aggregates and solvents. The magnetic microcapsules made of such aggregates are applied to writing panels to improve the clarity and contrast of the handwriting on the display panel. However, the wall material formed by gelatin and other anionic polymers through electrostatic action tends to be flexible after cross-linking. It is difficult to improve the strength of the wall material by cross-linking using ordinary curing agents such as glutamine transaminase. If used in a magnetic handwriting board, it is very likely to cause the internal magnetic microcapsule wall to break when writing vigorously, affecting the clarity. In addition, in order to improve the suspension and blackness of the magnetic particles, the method adopted in the CN117732384 patent application document is to improve the performance by lipophilic modification of the magnetic particles. This method increases the steps of product production and is only suitable for magnetic particles with smaller particle sizes. The magnetic particles prepared by modification have low stability in the system, which is easy to affect the product quality. Summary of the invention

[0005] In view of this, the embodiments of the present invention provide a magnetic microcapsule for preventing particle sedimentation, a preparation method thereof, and a magnetic film, so as to solve the problems of low writing fluency and poor trace durability due to particle sedimentation and aggregation in the prior art.

[0006] In a first aspect, an embodiment of the present invention provides a magnetic microcapsule for preventing particle sedimentation, wherein the magnetic microcapsule comprises a wall material and a core material, wherein the wall material is a mixture of anionic polymers and cationic polymers, and the core material is a mixture of magnetic particles, non-magnetic particles, an oily solvent, and a suspension stabilizer; the suspension stabilizer comprises any one or more of phthalate, polyamide wax, polysiloxane, sorbitan oleate, sorbitan monostearate, silicon dioxide, aluminum magnesium silicate, and lithium magnesium silicate; wherein the cationic polymer comprises one or two of gelatin, ε-polylysine, The anionic polymer comprises one or more of sodium carboxymethyl cellulose, gum arabic, and sodium alginate; the magnetic particles comprise nano-ferroferric oxide, and also comprise one or two of lipophilic nano-ferrite and nano-NdFeB, wherein the magnetic strengths of the nano-ferroferric oxide, the nano-ferrite, and the nano-NdFeB are different; the non-magnetic particles are lipophilic nano-titanium dioxide; the nano-ferrite in the magnetic particles comprises one or more of nano-manganese-zinc ferrite, nano-nickel-zinc ferrite, nano-magnesium-manganese ferrite, nano-aluminum-manganese ferrite, etc.

[0007] Preferably, the cationic polymer and the anionic polymer in the wall material are gelatin and gum arabic respectively, the core material includes nano-ferroferric oxide, the nano-ferrite and the nano-titanium dioxide, the oily solvent includes white oil and paraffin; the suspension stabilizer includes any one or more of phthalate, polyamide wax, polysilicone ether, sorbitan oleate, sorbitan monostearate, silicon dioxide, magnesium aluminum silicate, and magnesium lithium silicate.

[0008] Preferably, the cationic polymer and the anionic polymer in the wall material are ε-polylysine and gum arabic respectively, the core material comprises nano-ferroferric oxide, the nano-ferrite and the nano-titanium dioxide, and the oily solvent comprises white oil and paraffin.

[0009] Preferably, the mass ratio of the gelatin to the gum arabic is 1:0.8-1.2; the mass ratio of the nano-ferroferric oxide, the nano-ferrite and the nano-titanium dioxide is 1:1.5-3:9; and the mass ratio of the white oil to the paraffin is 1:7-9.

[0010] Preferably, the suspension stabilizer is a mixture of polyamide wax and sorbitan oleate, or a mixture of phthalate and polyamide wax, or a mixture of polysiloxane and silicon dioxide.

[0011] In a second aspect, an embodiment of the present invention provides a method for preparing magnetic microcapsules that prevent particle sedimentation, which is used to prepare the magnetic microcapsules as described above, comprising the following steps:

[0012] adding magnetic particles and non-magnetic particles to an oily solvent in a predetermined mass ratio to obtain an oil phase mixture;

[0013] Adding 0.1-2 wt% of a suspension stabilizer to the oil phase mixture and dispersing the mixture in a high-speed disperser at room temperature for 60-90 minutes to obtain a core material suspension;

[0014] Adding the cationic polymer and the anionic polymer into deionized water according to a preset mass ratio to obtain an aqueous phase solution;

[0015] Adding the core material suspension into the aqueous phase solution, and dispersing the core material suspension by stirring to obtain a dispersion;

[0016] An acid-base regulator is added to the dispersion to adjust the pH to a preset value. After reacting for a first preset time, a curing agent is added and the reaction is continued for a second preset time to obtain magnetic microcapsules.

[0017] Preferably, the magnetic particles include nano-iron tetroxide, and the magnetic particles also include one or both of nano-ferrite or nano-NdFeB;

[0018] The step of adding the magnetic particles and the non-magnetic particles to the oily solvent in a predetermined mass ratio to obtain an oil phase mixture comprises:

[0019] Nano ferrite, nano ferroferric oxide and nano titanium dioxide are added into an oily solvent in a mass ratio of 1:1.5 to 3:9 to obtain an oil phase mixture, wherein the oily solvent comprises white oil and paraffin in a mass ratio of 1:7 to 9.

[0020] Preferably, the adding of 0.1-2 wt% suspension stabilizer to the oil phase mixture and dispersing the mixture in a high-speed disperser at room temperature for 60-90 minutes to obtain a core material suspension comprises:

[0021] First, add 0.5-0.8 wt% of a mixture of polyamide wax and sorbitan oleate to the oil phase mixture, and disperse it in a high-speed disperser at a speed of 1800-2000 rpm for 20-30 minutes at room temperature;

[0022] Add 0.4-0.8 wt% of a mixture of phthalate and polysiloxane, and continue to disperse at a speed of 1200-1500 rpm for 20-30 minutes at room temperature;

[0023] 0.1-0.4 wt% of silicon dioxide is added, and the mixture is dispersed at a speed of 1000-1200 rpm for 20-30 minutes at room temperature to obtain the core material suspension.

[0024] Preferably, the step of adding the cationic polymer and the anionic polymer to deionized water at a preset mass ratio to obtain an aqueous solution comprises: adding gelatin and gum arabic to deionized water at a mass ratio of 1:0.8 to 1.2 to obtain an aqueous solution;

[0025] The step of adding the core material suspension to the aqueous solution and dispersing the core material suspension by stirring to obtain a dispersion comprises: adding the core material suspension to the aqueous solution at a ratio of 1:7 to 10, and using a stirring paddle to suspend and disperse at a rotation speed of 200 to 800 rpm to obtain the dispersion;

[0026] The step of adding an acid-base regulator to the dispersion to adjust the pH to a preset value, reacting for a first preset time, adding a curing agent, and continuing the reaction for a second preset time to obtain the magnetic microcapsules comprises: adding glacial acetic acid as an acid-base regulator to the dispersion to adjust the pH to 4.4-4.5, reacting for 0.5-1 hour, adding glutaraldehyde as a curing agent, and continuing the reaction for 0.5-1 hour to obtain the magnetic microcapsules.

[0027] In the third aspect, an embodiment of the present invention further provides a magnetic film, comprising a PET substrate layer, a rubber-based self-adhesive layer located on the PET substrate layer, a water-based glue and magnetic microcapsule mixed layer located on the rubber-based self-adhesive layer, and an AG PET film layer on the water-based glue and magnetic microcapsule layer; the thickness of the AG PET film is 0.1 to 0.14 mm; the water-based glue comprises any one or more of a PVA aqueous solution, a polyurethane, an ultraviolet absorber, and a leveling agent, wherein the magnetic microcapsules are the magnetic microcapsules described in the first aspect or the magnetic microcapsules prepared by the preparation method described in the second aspect.

[0028] In summary, the beneficial effects of the present invention are as follows:

[0029] The embodiment of the present invention provides a magnetic microcapsule for preventing particle sedimentation, a preparation method thereof and a magnetic film, wherein the magnetic microcapsule comprises a wall material and a core material, wherein the wall material is a mixture of anionic polymers and cationic polymers, and the core material is a mixture of magnetic particles, non-magnetic particles, an oily solvent and a suspension stabilizer; the suspension stabilizer comprises any one or more of phthalate, polyamide wax, polysiloxane, sorbitan oleate, sorbitan monostearate, silicon dioxide, magnesium aluminum silicate and magnesium lithium silicate; wherein the cationic polymer comprises one of gelatin, ε-polylysine or two, the anionic polymer includes one or more of sodium carboxymethyl cellulose, gum arabic, and sodium alginate; the magnetic particles include nano-iron tetroxide, and also include one or two of lipophilic nano-ferrite and nano-NdFeB, wherein the magnetic strengths of the nano-iron tetroxide, the nano-ferrite and the nano-NdFeB are different from each other; the non-magnetic particles are lipophilic nano-titanium dioxide; the nano-ferrite in the magnetic particles includes one or more of nano-manganese-zinc ferrite, nano-nickel-zinc ferrite, nano-magnesium-manganese ferrite, nano-aluminum-manganese ferrite, etc. The present invention forms a stable cross-linked grid structure and an electrostatic adsorption layer in the oil phase mixture by adding a suspension stabilizer, preventing the magnetic particles and non-magnetic particles from settling and aggregating, and ensuring the writing fluency and trace persistence; the magnetic microcapsules prepared by the magnetic microcapsule preparation method can significantly improve the performance of magnetic films and writing boards in terms of blackness, contrast and stability, making them better adapted to various application scenarios such as education, office, family, and business. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings required for use in the embodiment of the present invention will be briefly introduced below. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work, and these are all within the protection scope of the present invention.

[0031] Figure 1 is an image of the magnetic microcapsule in the embodiment of the present invention under an optical microscope.

[0032] Figure 2 This is an image of existing magnetic microcapsules under an optical microscope.

[0033] Figure 3 It is a schematic diagram showing that the magnetic microcapsules according to an embodiment of the present invention remain intact under a writing strength of 600 g.

[0034] Figure 4 It is a schematic diagram of the capsule wall damage of the existing magnetic microcapsule under the writing strength of 600g.

[0035] Figure 5Schematic diagram of the structure of the magnetic microcapsule according to the embodiment of the present invention.

[0036] Figure 6 It is a schematic diagram of the magnetic microcapsule presenting writing handwriting according to an embodiment of the present invention.

[0037] Figure 7 It is a schematic diagram of clearing handwriting by adjusting the magnetic strength according to an embodiment of the present invention.

[0038] Figure 8 It is a schematic diagram of the magnetic particles and non-magnetic particles uniformly dispersed in the capsule core according to an embodiment of the present invention.

[0039] Figure 9a Schematic diagram of the magnetic microcapsule of Example 1 of the present invention.

[0040] Figure 9b Schematic diagram of a magnetic film according to Example 1 of the present invention.

[0041] Fig.10a Schematic diagram of the magnetic microcapsule of Example 2 of the present invention.

[0042] Fig.10b It is a schematic diagram of a magnetic film according to Example 2 of the present invention.

[0043] Fig.11a Schematic diagram of the magnetic microcapsule of Example 3 of the present invention.

[0044] Fig.11b It is a schematic diagram of a magnetic film according to Example 3 of the present invention.

[0045] Fig.12a Schematic diagram of the magnetic microcapsule of Example 4 of the present invention.

[0046] Figure 12b It is a schematic diagram of a magnetic film according to Example 4 of the present invention.

[0047] Fig.13a Schematic diagram of the magnetic microcapsule of Example 5 of the present invention.

[0048] Fig.13b It is a schematic diagram of a magnetic film according to Example 5 of the present invention.

[0049] Fig.14a Schematic diagram of the magnetic microcapsule of Comparative Example 1 of the present invention.

[0050] Fig.14b Schematic diagram of a magnetic film of Comparative Example 1 of the present invention.

[0051] Fig.15a Schematic diagram of the magnetic microcapsule of Comparative Example 2 of the present invention.

[0052] Fig.15bSchematic diagram of a magnetic film of Comparative Example 2 of the present invention.

[0053] Fig.16 It is a schematic diagram of the magnetic film of Comparative Example 3 of the present invention.

[0054] Fig.17 Schematic diagram of a magnetic film of Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0055] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.

[0056] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0057] The first aspect of the present invention provides a magnetic microcapsule, which includes a wall material and a core material, wherein the wall material is a mixture of anionic polymers and cationic polymers, and the core material is a mixture of magnetic particles, non-magnetic particles, oily solvents, oil-phase anti-settling agents and suspension stabilizers; wherein the cationic polymer includes one or two of gelatin and ε-polylysine, and the anionic polymer includes one or more of sodium carboxymethyl cellulose, gum arabic and sodium alginate; the magnetic particles include nano-ferroferric oxide, and one or two of lipophilic nano-ferrite or nano-needymium iron boron; the non-magnetic particles are lipophilic nano-titanium dioxide (i.e., lipophilic nano-titanium dioxide); the oil-phase anti-settling agent includes at least KH550 (γ-aminopropyltriethoxysilane), KH560 (3-glycidoxypropyltrimethoxysilane), dodecyltrimethoxysilane, hexadecyltrimethoxysilane, bentonite, dilute hydrochloric acid and sodium hydroxide.

[0058] When the microcapsule wall is damaged, the magnetic particles cannot migrate upward in the dispersed fluid under the traction of the magnetic writing pen, which reduces the resolution of the handwriting and causes unclear handwriting. Therefore, in the above embodiment, the compounded anionic and cationic polymers are used as wall materials to wrap the core material and form a tough sphere with a spindle shape, which can significantly improve the strength of the wall material of the microcapsule, making it less likely to be damaged during the writing process. The increased strength enables the microcapsule to better protect the internal magnetic particles, avoid the inability of the particles to effectively migrate due to damage to the capsule wall, and ensure the clarity and stability of the handwriting; at the same time, there is no need to add other dispersing agents when preparing the microcapsules, saving raw materials and costs.

[0059] In the above embodiments, nano-iron tetroxide, nano-ferrite or nano-NdFeB with different magnetic strengths are mainly used as magnetic particles. By doping nano-iron tetroxide, nano-ferrite or nano-NdFeB in different proportions, the magnetic force can be adjusted to facilitate writing and erasing. In addition, by adjusting the proportion of different magnetic particles, the blackness can be adjusted, and then the writing contrast can be adjusted. For example, using magnetic particles with higher blackness or increasing their proportion can increase the blackness of writing, making the handwriting deeper and more obvious; or reasonably adjusting the proportion of different magnetic particles, so that the contrast between the blackness of the handwriting and the background is higher, thereby improving the visual effect of writing. The microcapsule magnetism of this embodiment can significantly improve the writing blackness, contrast and stability of the writing board.

[0060] Preferably, the nano ferrite in the magnetic particles includes one or more of nano manganese zinc ferrite, nano nickel zinc ferrite, nano magnesium manganese ferrite, nano aluminum manganese ferrite, etc. In other embodiments, it can also be other nano ferrites or ferrites. Nano manganese zinc ferrite has high magnetic permeability and saturation magnetization, so that the magnetic microcapsule can respond quickly under the external magnetic field and improve the surging property; while the high resistivity and low hysteresis loss of nano nickel zinc ferrite can maintain excellent magnetic properties in a wide frequency range, so that the microcapsule can respond quickly under magnetic fields of different frequencies; magnesium manganese ferrite maintains stable magnetic properties under different temperature conditions, ensuring that the microcapsule can respond quickly at various temperatures, and nano magnesium manganese ferrite has a lower density, which can reduce the overall mass of the microcapsule and improve the surging property, and is suitable for lightweight and high response speed applications; nano aluminum manganese ferrite has high hardness and wear resistance, which can improve the mechanical strength of the microcapsule, so that it can maintain stable surging property in high-frequency use, and by adjusting the ratio of aluminum and manganese, the magnetic properties of the ferrite can be accurately controlled, thereby optimizing the surging property of the microcapsule.

[0061] Different types of nanoferrites have different magnetic properties, which can significantly improve the response speed and sensitivity of magnetic microcapsules in external magnetic fields and meet the needs of fast writing and erasing; the excellent mechanical strength, wear resistance and temperature stability of nanoferrites ensure the long-term stability and efficient response of magnetic microcapsules in various environments; by selecting different nanoferrites, the mobility and stability of magnetic microcapsules can be optimized according to specific application requirements, thereby improving their overall performance and application effects.

[0062] Preferably, the oily solvent is one or more of white oil, glyceryl caprylate, paraffin, dioctyl terephthalate, turpentine, transformer oil, polyalphaolefin synthetic oil. The components in the oily solvent such as white oil, glyceryl caprylate, paraffin, dioctyl terephthalate, turpentine, transformer oil, polyalphaolefin synthetic oil, etc. can effectively adjust the polarity of the solution, ensure that the magnetic particles and non-magnetic particles are stably and evenly dispersed in the system, form a stable oil phase environment, and improve the performance and service life of the writing board. Preferably, the oily solvent is a mixture of white oil and paraffin. The mixing of white oil and paraffin can provide a chemically stable and structurally stable oil phase environment, ensuring the uniform dispersion and stable existence of magnetic and non-magnetic particles in the whole system. The film-forming property of paraffin and the lubricity of white oil are combined to enhance the structural strength of the microcapsules, while maintaining good fluidity, and are suitable for writing and erasing applications.

[0063] Preferably, the suspension stabilizer includes any one or more of phthalate, polyamide wax, polysilicone, sorbitan oleate, sorbitan monostearate, silicon dioxide, magnesium aluminum silicate, and lithium magnesium silicate. Preferably, the suspension stabilizer is a mixture of polyamide wax and sorbitan oleate. Polyamide wax has good dispersibility and stability, and can form a cross-linked grid structure to prevent particle sedimentation. Sorbitan oleate is an excellent emulsifier and stabilizer that can enhance the stable dispersion of particles. In other embodiments, the suspension stabilizer can also be a mixture of phthalate and polyamide wax, or a mixture of polysilicone and silicon dioxide. The suspension stabilizer can form a stable cross-linked grid structure in the oil phase solvent. The cross-linked grid structure helps prevent the magnetic particles and non-magnetic particles from settling or aggregating, ensuring that they are evenly dispersed in the oil phase. The suspension stabilizer can also form a stable electrostatic adsorption layer on the surface of the particles. The formation of the electrostatic adsorption layer helps to improve the dispersibility of the particles, allowing the magnetic particles and non-magnetic particles to be evenly dispersed in the oil phase. The evenly dispersed particles help to improve the smoothness of writing. In addition, through the stable cross-linked grid structure and electrostatic adsorption layer, the arrangement of the particles after writing is more stable, allowing the writing marks to be maintained for a long time, ensuring that the writing marks will not fade or blur easily. This feature is particularly important for application scenarios that require the writing content to be preserved for a long time.

[0064] like Figure 1 The image of the magnetic microcapsule of the embodiment of the present invention obtained under an optical microscope is shown. Figure 2 Shown are images of other existing magnetic microcapsules. Figure 1 The wall material of the magnetic microcapsules is mainly composed of gelatin (cationic polymer) and gum arabic (anionic polymer). Changing the ratio of cationic polymer (such as gelatin) and anionic polymer (such as gum arabic) can change the ball formation rate and viscosity of the magnetic microcapsules. Figure 1 and Figure 2 It can be seen that the wall thickness of the magnetic microcapsules provided in the embodiment of the present invention is significantly greater than Figure 2 The wall material thickness of the magnetic microcapsule is as follows, so as to ensure that the magnetic microcapsule is not easily damaged during the writing process, and Figure 1 The overall shape of the magnetic microcapsules is similar to that of a shuttle. This shuttle-shaped spherical shape can ensure that the magnetic microcapsules can withstand greater writing strength (the average writing strength can be 700-800g, while the maximum writing strength that the existing magnetic microcapsules can withstand is 500g). Figure 3 As shown in FIG. 1 , the magnetic microcapsules of the present invention are still intact under the condition of a writing strength of 600 g, while Figure 4 As shown, other existing magnetic microcapsules suffered more serious damage under the same writing intensity.

[0065] like Figure 5FIG. 2 is a schematic diagram of the structure of a magnetic microcapsule according to an embodiment of the present invention. The capsule core of the magnetic microcapsule is wrapped by a capsule wall, wherein the capsule core includes magnetic particles (such as Figure 5 black particles) and non-magnetic particles (such as Figure 5 In the embodiment of the present invention, the magnetic particles include nano-iron tetroxide for achieving writing blackness and oleophilic nano-ferrite for achieving surge (wherein surge is also called magnetic surge or writing surge, which is used to characterize the response time or speed of magnetic particles under the action of an external magnetic field. Good surge means that the magnetic particles have a fast response time or a fast speed, which is specifically manifested as a fast / high erasing speed in the magnetic film). Adjusting the proportion of nano-iron tetroxide can adjust the writing blackness, adjusting the proportion of oleophilic nano-ferrite can adjust the writing surge, and the non-magnetic particles are oleophilic nano-titanium dioxide. Adjusting the proportion of oleophilic nano-titanium dioxide can adjust the whiteness of the magnetic film. Figure 5 As shown in the figure, in the unwritten state, the black magnetic particles are wrapped in the center by the white nano-titanium dioxide, and the magnetic film or writing board is white. When writing with a writing pen, Figure 6 As shown in the figure, the magnetic particles in the magnetic microcapsules are gathered above the sphere under the magnetic force of the writing pen, thus showing a black note. Figure 7 As shown, the magnetic particles move or disperse toward the bottom of the sphere under the action of the external magnetic force. Generally, the higher the external magnetic force, the greater the dispersion of the magnetic particles, and the better the erasing effect. The lower the magnetic force, the smaller the dispersion of the magnetic particles, and the worse the erasing effect. When the external magnetic force is constant, the higher the mobility of the magnetic microcapsules, the greater the dispersion of the magnetic particles, and the better the erasing effect. The lower the mobility, the smaller the dispersion of the magnetic particles, and the worse the erasing effect. When the external magnetic force is constant, the higher the mobility of the magnetic microcapsules, the greater the dispersion of the magnetic particles, and the better the erasing effect. The lower the mobility, the smaller the dispersion of the magnetic particles, so that the writing traces will still remain on the surface of the writing board, and the erasing effect is poor. In an embodiment of the present invention, the writing mobility of the magnetic microcapsules can be adjusted by adjusting the proportion of the oleophilic nanoferrite. The better the mobility, the easier it is for the magnetic particles to be dispersed under the magnetic force of the eraser pen. By adjusting the magnetic strength and conversion frequency of the eraser pen, the writing content can be cleanly and quickly removed.

[0066] In the embodiment of the present invention, a suspension stabilizer is added to the core material to ensure that the magnetic particles and non-magnetic particles are stably and evenly dispersed in the system, thereby achieving an excellent anti-settling effect and improving the performance and service life of the writing board. Figure 8 As shown, after the magnetic microcapsules are formed into films, the magnetic particles and non-magnetic particles are evenly distributed, and the anti-settling property is good. In one example, the magnetic film prepared by the magnetic microcapsules provided by the embodiment of the present invention is placed in a high temperature of 50° (under this temperature condition, one week of baking is equivalent to half a year of sedimentation, and 2 weeks is equivalent to one year of sedimentation). After baking for 2 weeks, the magnetic film can still be written and erased normally, indicating that the magnetic film can resist one year of sedimentation.

[0067] In addition, the test results show that the blackness value of the magnetic film can reach 0.69 and the whiteness value is 0.2 (the blackness value of other existing magnetic films is about 0.4-0.5). In writing or display applications, magnetic films with high blackness can provide clearer and more contrasting writing effects, which is especially important for devices such as electronic paper and erasable whiteboards.

[0068] The second aspect of the present invention provides a method for preparing magnetic microcapsules, comprising the following steps:

[0069] adding magnetic particles and non-magnetic particles to an oily solvent according to a preset mass ratio to obtain an oil phase mixture;

[0070] After adding a suspension stabilizer to the oil phase mixture, dispersing the mixture at a preset dispersing speed to obtain a core material suspension;

[0071] Adding the cationic polymer and the anionic polymer into deionized water according to a preset mass ratio to obtain an aqueous phase solution;

[0072] Adding the core material suspension into the aqueous phase solution, and dispersing the core material suspension by stirring to obtain a dispersion;

[0073] An acid-base regulator is added to the dispersion to adjust the pH to a preset value. After reacting for a first preset time, a curing agent is added and the reaction is continued for a second preset time to obtain magnetic microcapsules.

[0074] Preferably, the cationic polymer includes one or two of gelatin and ε-polylysine, the anionic polymer includes one or more of sodium carboxymethyl cellulose, gum arabic, and sodium alginate; the magnetic particles include nano-ferroferric oxide with different magnetic strengths, and also include one or two of oleophilic nano-ferrite or nano-needymium iron boron; the non-magnetic particles are oleophilic nano-titanium dioxide.

[0075] Preferably, the oily solvent is one or more of white oil, caprylic glyceride, paraffin, dioctyl terephthalate, turpentine, transformer oil, and poly-alpha-olefin synthetic oil.

[0076] Preferably, the suspension stabilizer includes any one or more of phthalate, polyamide wax, polysiloxane, sorbitan oleate, sorbitan monostearate, silicon dioxide, magnesium aluminum silicate, and magnesium lithium silicate.

[0077] In one embodiment, in the method for preparing the magnetic microcapsules, adding the magnetic particles and the non-magnetic particles to the oily solvent at a predetermined mass ratio to obtain an oil phase mixture comprises:

[0078] Adding nano ferrite, nano ferroferric oxide and nano titanium dioxide into an oily solvent in a mass ratio of 1:1.5 to 3:9 to obtain an oil phase mixture, wherein the oily solvent comprises white oil and paraffin in a mass ratio of 1:7 to 9;

[0079] Specifically, adjusting the proportion of nano-ferroferric oxide can adjust the writing blackness, adjusting the proportion of nano-ferrite can adjust the magnetic surge, and adjusting nano-titanium dioxide can adjust the whiteness. The combination of nano-ferrite, nano-ferroferric oxide, and nano-titanium dioxide in a mass ratio of 1:1.5 to 3:9 can obtain excellent blackness, whiteness, and surge. The low viscosity and chemical stability of white oil are combined with the high melting point and film-forming properties of paraffin. The white oil and paraffin in a mass ratio of 1:7 to 9 form a stable oil phase mixture, ensuring the uniform dispersion and long-term stability of magnetic and non-magnetic particles.

[0080] After adding a suspension stabilizer to the oil phase mixture and dispersing it at a preset dispersing speed, a core material suspension is obtained, which includes:

[0081] Adding 0.1-2 wt% of a suspension stabilizer to the oil phase mixture and dispersing the mixture in a high-speed disperser at 25° C. for 60-90 minutes to obtain a core material suspension;

[0082] Specifically, 0.1-2 wt% of suspension stabilizers such as polyamide wax and sorbitan oleate provide dispersibility and stability, ensuring uniform distribution of particles in the oil phase and preventing sedimentation. Dispersion conditions of 25°C maintain fluidity of the system, and a dispersion time of 60-90 minutes ensures adequate mixing.

[0083] The step of adding the cationic polymer and the anionic polymer into deionized water according to a preset mass ratio to obtain an aqueous solution comprises:

[0084] Add gelatin and gum arabic into deionized water at a mass ratio of 1:0.8-1.2 to obtain an aqueous solution;

[0085] Specifically, gelatin and gum arabic as cationic and anionic polymers can form a stable wall material structure. The ratio of 1:0.8 to 1.2 ensures that the formed microcapsule shell wall has appropriate strength and flexibility.

[0086] The step of adding the core material suspension into the aqueous phase solution and dispersing the core material suspension by stirring to obtain a dispersion comprises:

[0087] The core material suspension is added to the aqueous phase solution at a ratio of 1:7-10, and a stirring paddle is used to suspend and disperse at a rotation speed of 200-800 rpm to obtain the dispersion;

[0088] Specifically, the core material suspension is added to the aqueous phase solution at a ratio of 1:7-10, and stirred and dispersed at a rotation speed of 200-800 rpm, which can ensure uniform distribution of the core material in the aqueous phase and prevent aggregation.

[0089] The step of adding an acid-base regulator, glacial acetic acid, to the dispersion to adjust the pH to a preset value, reacting for a first preset time, adding a curing agent, glutaraldehyde, and continuing to react for a second preset time to obtain magnetic microcapsules comprises:

[0090] Glacial acetic acid as an acid-base regulator is added to the dispersion to adjust the pH value to 4.4-4.5. After reacting for 0.5-1 hour, glutaraldehyde as a curing agent is added and the reaction is continued for 0.5-1 hour to obtain magnetic microcapsules.

[0091] Specifically, glacial acetic acid is used to adjust the pH to a suitable range of 4.4 to 4.5 to ensure the stable reaction of anionic and cationic polymers and form a uniform microcapsule wall material. Glutaraldehyde is used as a cross-linking agent to enhance the strength and stability of the wall material and prevent the wall from breaking during the writing process. The reaction time of 0.5 to 1 hour ensures sufficient cross-linking.

[0092] In one embodiment, the adding of 0.1-2 wt% suspension stabilizer to the oil phase mixture and dispersing the mixture in a high-speed disperser at 25° C. for 60-90 minutes to obtain a core material suspension comprises:

[0093] First, add 0.5-0.8 wt% of a mixture of polyamide wax and sorbitan oleate to the oil phase mixture, and disperse it in a high-speed disperser at 1800-2000 rpm for 20-30 minutes at 25° C.;

[0094] Then, 0.4-0.8 wt% of a mixture of phthalate and polysiloxane was added, and the mixture was dispersed at 1200-1500 rpm for 20-30 minutes at 25°C.

[0095] Finally, 0.1-0.4 wt % of silicon dioxide is added, and the mixture is dispersed at 1000-1200 rpm for 20-30 minutes at 25° C. to obtain the core material suspension.

[0096] The preparation of the core material suspension is divided into three stages. First, a mixture of polyamide wax and sorbitan oleate is added. Polyamide wax has good dispersibility and stability, and can form a cross-linked grid structure in the oil phase to enhance the dispersion effect of particles and prevent sedimentation and aggregation. Sorbitan oleate is an excellent emulsifier and stabilizer, which can form a stable adsorption layer on the surface of particles, further improving the dispersion and stability of particles. First, polyamide wax and sorbitan oleate are evenly distributed in the oil phase through efficient dispersion to form a stable dispersion system, laying the foundation for the subsequent addition of stabilizers. In the second stage, a mixture of phthalates and polysiloxane is added. Because phthalates have good wettability and dispersibility, they can effectively reduce the viscosity of the system, enhance the fluidity of the oil phase, and further improve the dispersion effect of particles. Polysiloxane has good emulsification and stability properties, and can form a stable adsorption layer on the surface of particles to prevent secondary aggregation of particles. In the second stage, the dispersion speed is appropriately reduced to make phthalates and polysiloxane more fully mixed with the oil phase to form a more stable dispersion system and improve the fluidity and stability of the system. Finally, silicon dioxide is added. Silica has good adsorption and stabilization effects and can form a stable electrostatic adsorption layer on the surface of the particles, further improving the dispersibility and anti-sedimentation performance of the particles. In the third stage, the dispersion speed is reduced to make the silicon dioxide more evenly distributed in the system, further improving the dispersibility and anti-sedimentation performance of the particles and ensuring the long-term stability of the microcapsules.

[0097] By adding different types of suspension stabilizers in stages, each step can make the specific stabilizer fully play its role, gradually enhancing the dispersion effect of the particles. In addition, the combination of multiple suspension stabilizers forms a multi-layer protection to ensure the long-term stability of the particles in the system and prevent sedimentation and aggregation. The use of stabilizers such as silica and polyamide wax has formed a good anti-sedimentation effect, ensuring the stability of the microcapsules during long-term storage and use. The addition of phthalates and polysiloxanes improves the fluidity of the system, reduces the viscosity, and is conducive to subsequent stirring and dispersion operations. Through the above-mentioned staged addition steps, the dispersibility, stability and anti-sedimentation performance of the magnetic microcapsules can be significantly improved, thereby improving the overall quality and application effect of the microcapsules.

[0098] In one embodiment, the magnetic particles include: nano-iron tetroxide, and one or two of nano-ferrite and nano-NdFeB, and the non-magnetic particles include nano-titanium dioxide;

[0099] The step of adding the magnetic particles and the non-magnetic particles to the oily solvent in a predetermined mass ratio to obtain an oil phase mixture comprises:

[0100] Dissolving a polyurethane precursor in a preset solvent to obtain a polyurethane solution, wherein the polyurethane precursor includes one of aromatic polyurethane, aliphatic polyurethane or aqueous polyurethane, and the preset solvent includes dimethyl sulfoxide or ethanol;

[0101] Specifically, polyurethane precursor is the basic substance for forming polyurethane, which can be mixed with solvent to form a solution. Aromatic polyurethane has high strength and wear resistance, aliphatic polyurethane has good flexibility and transparency, and water-based polyurethane is environmentally friendly and safe. Dimethyl sulfoxide and ethanol are both commonly used organic solvents that can dissolve polyurethane precursors well to form a uniform polyurethane solution.

[0102] Washing the magnetic particles and the non-magnetic particles with ethanol and drying them;

[0103] Ethanol is an effective cleaning agent that can remove impurities and contaminants from the surface of magnetic and non-magnetic particles to ensure that their surface is clean. The cleaned particles need to be dried to remove residual ethanol to avoid affecting subsequent steps. The dried particle surface is more conducive to the coating reaction with the polyurethane precursor in the polyurethane solution.

[0104] adding the washed and dried magnetic particles and the non-magnetic particles into the polyurethane solution to obtain a mixed solution;

[0105] The washed and dried particles are added to the polyurethane solution separately to ensure that each particle is evenly dispersed in the solution. This step is to allow the polyurethane precursor to fully contact the particle surface and prepare for the subsequent coating reaction.

[0106] According to a preset reaction time and a preset reaction temperature, the mixed solution is stirred to coat the surfaces of the magnetic particles and the non-magnetic particles with polyurethane, wherein the preset reaction time is 1 to 4 hours and the preset reaction temperature is 60 to 80° C.;

[0107] According to the preset reaction time and the preset reaction temperature, the mixed solution is stirred to coat the surface of the magnetic particles and the non-magnetic particles with polyurethane. The preset reaction time is 1 to 4 hours, and the preset reaction temperature is 60 to 80°C. The mixed solution is stirred at the preset temperature and time, and the polyurethane precursor forms a coating layer on the surface of the particles. The control of temperature and time is key. The temperature range of 60 to 80°C can promote the reaction and curing of the polyurethane precursor to form a uniform coating layer, and the reaction time of 1 to 4 hours ensures the stability and integrity of the coating layer.

[0108] The coated magnetic particles and the coated non-magnetic particles are added to the oily solvent according to the predetermined mass ratio to obtain the oil phase mixture.

[0109] Specifically, the coated particles are finally added to the oily solvent according to a predetermined mass ratio to form a final oil phase mixture. The coated particles have a polyurethane layer on their surface, which can significantly improve their dispersibility and stability in the oily solvent, avoid agglomeration between particles, and ensure the uniformity and long-term stability of the oil phase mixture.

[0110] Preferably, the steps of preparing the oil phase anti-settling agent include:

[0111] Step 1, add 5 parts of bentonite to 94.8 parts of water, stir with magnetic stirring at 500 rpm, room temperature, and stir for 100 minutes;

[0112] Step 2: Add 0.1 parts of KH550 to the solution treated in step 1, and continue stirring at 500 rpm for 5 minutes;

[0113] Step 3: Use dilute hydrochloric acid to adjust the pH of the solution treated in step 2 to 4.5-5, and continue stirring at 500 rpm for 30 min;

[0114] Step 4: Use sodium hydroxide to adjust the pH of the solution treated in step 3 to 8-8.5, heat it in a water bath to 60-70°C and continue stirring at 500 rpm for 60 min;

[0115] Step 5: Filter and dry the solution treated in step 4 to obtain modified bentonite, which is used as an oil phase anti-settling agent.

[0116] The third aspect of the present invention provides a magnetic film, which includes a PET substrate layer, a rubber-based self-adhesive layer located on the PET substrate layer, a water-based glue and magnetic microcapsule mixed layer located on the rubber-based self-adhesive layer, and an AG PET film layer on the water-based glue and magnetic microcapsule mixed layer; the magnetic microcapsules are as described in the first and second aspects above.

[0117] Preferably, the AG PET film has a thickness of 0.1 to 0.14 mm, a haze of 28% to 29%, and a hardness of 4H.

[0118] Preferably, the water-based glue includes any one or more of a PVA aqueous solution, a polyurethane, an ultraviolet absorber, and a leveling agent.

[0119] The magnetic film can be used in education, office, business and retail fields, etc. For example, it can be used to display course content in teaching; it can be used to explain, discuss and record important information in training classes and meetings; students can use portable writing boards to take notes, practice writing and review at home; it can be used in restaurants, cafes and retail stores to display daily specials, menus and promotional information, etc.

[0120] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0121] Example 1

[0122] 1. Preparation of magnetic microcapsules

[0123] Add 1 g of nano ferrite with an average particle size of 400 nm to 800 nm, 1.5 g of nano ferroferric oxide with an average particle size of 200 nm to 500 nm, and 9 g of titanium dioxide with an average particle size of 200 nm to 500 nm in a mass ratio of 1:1.5:9 to an oily solvent of 1 g of white oil and 7 g of paraffin in a mass ratio of 1:7 to obtain an oil phase mixture;

[0124] After adding 0.1 wt % of a suspension stabilizer to the oil phase mixture, the oil phase mixture was dispersed in a high-speed disperser at 25° C. for 60 minutes to obtain a core material suspension;

[0125] Add 1 g of gelatin and 1 g of sodium carboxymethyl cellulose into 100 g of deionized water to obtain an aqueous phase solution;

[0126] The core material suspension is added to the aqueous phase solution at a mass ratio of 1:7, and a stirring paddle is used to suspend and disperse at a rotation speed of 500 rpm to obtain a dispersion;

[0127] An acid-base regulator, glacial acetic acid, was added to the dispersion to adjust the pH to 4.5. After reacting for 0.5 hours, 1 g of curing agent glutaraldehyde was added and the reaction was continued for 0.5 hours to obtain magnetic microcapsules.

[0128] 2. Preparation of magnetic film

[0129] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 6:4, and stirred at a speed of 1500rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AGPET film with a thickness of 0.12mm using a coating machine, and the coating thickness was 0.35mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the water-based glue and microcapsule coating mixture away from the AG PET to obtain a magnetic film.

[0130] Preferably, after forming the microcapsule coating on the AG PET film, the AG PET film coated with the microcapsule coating can also be screen printed with a mesh of 30 meshes, and cut into the size required for making a writing board, and then the rubber-based adhesive and the PET substrate are attached to obtain a magnetic film.

[0131] In this embodiment, Figure 9a The schematic diagram of the magnetic microcapsules prepared in this example under a microscope is shown in FIG. Figure 9b The figure shows the contrast effect of writing on the magnetic film made of the magnetic microcapsules. Figure 9a As shown in the figure, the magnetic microcapsules have a high balling rate, and are relatively uniform in shape and size. Most of the magnetic microcapsules are dispersed and not aggregated, but a small number of magnetic microcapsules are aggregated together (as shown in the lower right corner of the image) with medium viscosity. Figure 9b The magnetic film shown has a medium blackness and a medium writing contrast. Since the proportion of magnetic particles in the nano-ferrite is relatively high, its surging property is optimized, and a high average erasing speed result is obtained when an eraser pen is used for a handwriting erasure test.

[0132] Example 2

[0133] 1. Preparation of magnetic microcapsules

[0134] Add 1 g of nano ferrite with an average particle size of 400 nm to 800 nm, 2 g of nano ferroferric oxide with an average particle size of 200 nm to 500 nm, and 9 g of titanium dioxide with an average particle size of 200 nm to 500 nm in a mass ratio of 1:2:9 to an oily solvent of 1 g of white oil and 7 g of paraffin in a mass ratio of 1:7 to obtain an oil phase mixture;

[0135] After adding 1 wt % of a suspension stabilizer to the oil phase mixture, the oil phase mixture was dispersed in a high-speed disperser at 25° C. for 60 minutes to obtain a core material suspension;

[0136] Add 1 g of gelatin and 1 g of gum arabic to 100 g of deionized water to obtain an aqueous solution;

[0137] The core material suspension is added to the aqueous phase solution at a mass ratio of 1:7.5, and a stirring paddle is used to suspend and disperse at a rotation speed of 450 rpm to obtain a dispersion;

[0138] An acid-base regulator, glacial acetic acid, was added to the dispersion to adjust the pH to 4.5. After reacting for 1 hour, 1 g of curing agent, glutaraldehyde, was added and the reaction was continued for 0.5 hour to obtain magnetic microcapsules.

[0139] 2. Preparation of magnetic film

[0140] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 6:4, and stirred at a speed of 1500rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AGPET film with a thickness of 0.12mm using a coating machine, and the coating thickness was 0.35mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the water-based glue and microcapsule coating mixture away from the AG PET to obtain a magnetic film.

[0141] In this embodiment, the magnetic microcapsules have a high balling rate, low viscosity, high average erasing speed, and high writing contrast. Fig.10a The figure shows the schematic diagram of the prepared magnetic microcapsules under a microscope. Fig.10b Schematic diagram of the contrast effect of magnetic film writing made of the magnetic microcapsules is shown. Fig.10a As shown, the magnetic microcapsule balling rate is high, the size of the magnetic microcapsules is relatively uneven, and the large-size magnetic microcapsules and the small-size magnetic microcapsules each account for about half, but the magnetic microcapsules are dispersed and not aggregated, and the overall viscosity is low; since the proportion of nano-iron tetroxide in this embodiment is increased relative to that in Example 1, the increase in the number of magnetic particles can increase the blackness, so that its contrast is also improved relative to that in Example 1. Fig.10b The blackness of the magnetic film shown is higher than Figure 9b Medium magnetic film blackness, magnetic film writing contrast is also higher than Figure 9b Magnetic film in.

[0142] Example 3

[0143] 1. Preparation of magnetic microcapsules

[0144] Add 1 g of nano ferrite with an average particle size of 400 nm to 800 nm, 2 g of nano ferroferric oxide with an average particle size of 200 nm to 500 nm, and 9 g of titanium dioxide with an average particle size of 200 nm to 500 nm in a mass ratio of 1:2:9 to an oily solvent of 1 g of white oil and 9 g of paraffin in a mass ratio of 1:9 to obtain an oil phase mixture;

[0145] After adding 2 wt % of a suspension stabilizer to the oil phase mixture, the oil phase mixture was dispersed in a high-speed disperser at 25° C. for 60 minutes to obtain a core material suspension;

[0146] Add 1 g of gelatin and 1 g of gum arabic to 100 g of deionized water to obtain an aqueous solution;

[0147] The core material suspension is added to the aqueous phase solution at a mass ratio of 1:10, and a stirring paddle is used to suspend and disperse at a rotation speed of 450 rpm to obtain a dispersion;

[0148] An acid-base regulator, glacial acetic acid, was added to the dispersion to adjust the pH to 4.5. After reacting for 1 hour, 1 g of curing agent, glutaraldehyde, was added and the reaction was continued for 0.5 hour to obtain magnetic microcapsules.

[0149] 2. Preparation of magnetic film

[0150] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 6:4, and stirred at a speed of 1500rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AG PET film with a thickness of 0.12 using a coating machine, and the coating thickness was 0.35mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the mixed layer of water-based glue and microcapsules away from the AG PET to obtain a magnetic film.

[0151] In this embodiment, if Fig.11a The figure shows the schematic diagram of the prepared magnetic microcapsules under a microscope. Fig.11b Schematic diagram of the contrast effect of magnetic film writing made of the magnetic microcapsules is shown. Fig.11a As shown, the magnetic microcapsule balling rate is high, the size of the magnetic microcapsules is relatively uniform, and the magnetic microcapsules are dispersed without aggregation, and the overall viscosity is low; in addition, the proportion of nano-iron tetroxide in this embodiment is increased relative to that in Example 1, thereby increasing the blackness, such as Fig.11b The blackness of the magnetic film shown is significantly higher than Figure 9b The blackness of the magnetic film and the writing contrast of the magnetic film are also higher than Figure 9b Magnetic film in.

[0152] Example 4

[0153] 1. Preparation of magnetic microcapsules

[0154] Add 1 g of nano ferrite with an average particle size of 400 nm to 800 nm, 3 g of nano ferroferric oxide with an average particle size of 200 nm to 500 nm, and 9 g of titanium dioxide with an average particle size of 200 nm to 500 nm in a mass ratio of 1:3:9 to an oily solvent of 1 g of white oil and 9 g of paraffin in a mass ratio of 1:9 to obtain an oil phase mixture;

[0155] After adding 2 wt % of a suspension stabilizer to the oil phase mixture, the oil phase mixture was dispersed in a high-speed disperser at 25° C. for 60 minutes to obtain a core material suspension;

[0156] Add 1 g of polylysine and 1 g of gum arabic to 100 g of deionized water to obtain an aqueous solution;

[0157] The core material suspension is added to the aqueous phase solution at a mass ratio of 1:10, and a stirring paddle is used to suspend and disperse at a rotation speed of 450 rpm to obtain a dispersion;

[0158] An acid-base regulator, glacial acetic acid, was added to the dispersion to adjust the pH to 4.5. After reacting for 1 hour, 1 g of curing agent, glutaraldehyde, was added and the reaction was continued for 0.5 hour to obtain magnetic microcapsules.

[0159] 2. Preparation of magnetic film

[0160] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 6:4, and stirred at a speed of 1500rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AG PET film with a thickness of 0.12 using a coating machine, and the coating thickness was 0.35mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the mixed layer of water-based glue and microcapsules away from the AG PET to obtain a magnetic film.

[0161] In this embodiment, if Fig.12a The figure shows the schematic diagram of the prepared magnetic microcapsules under a microscope. Figure 12b Schematic diagram of the contrast effect of magnetic film writing made of the magnetic microcapsules is shown. Fig.12a As shown, the magnetic microcapsule balling rate is high and the size of the magnetic microcapsules is relatively uniform, but a small part of the magnetic microcapsules are aggregated and sticky, and the viscosity is medium; the viscosity will have a certain impact on the average erasing speed of the magnetic film. Although this embodiment improves the mass ratio of nano-iron tetroxide and thus increases the blackness and contrast of the magnetic film, the mass ratio of nano-ferrite in the magnetic particles is reduced relative to that of Examples 1-3, the magnetic surge mobility is reduced, and the average erasing speed is medium, which is slightly insufficient.

[0162] Example 5

[0163] 1. Preparation of magnetic microcapsules

[0164] Add 1 g of nano ferrite with an average particle size of 400 nm to 800 nm, 3 g of nano ferroferric oxide with an average particle size of 200 nm to 500 nm, and 9 g of titanium dioxide with an average particle size of 200 nm to 500 nm in a mass ratio of 1:3:9 to an oily solvent of 1 g of white oil and 8 g of paraffin in a mass ratio of 1:8 to obtain an oil phase mixture;

[0165] After adding 2 wt % of a suspension stabilizer to the oil phase mixture, the oil phase mixture was dispersed in a high-speed disperser at 25° C. for 60 minutes to obtain a core material suspension;

[0166] Add 1 g of polylysine and 1 g of gum arabic to 100 g of deionized water to obtain an aqueous solution;

[0167] The core material suspension is added to the aqueous phase solution at a mass ratio of 1:10, and a stirring paddle is used to suspend and disperse at a rotation speed of 500 rpm to obtain a dispersion;

[0168] An acid-base regulator, glacial acetic acid, was added to the dispersion to adjust the pH to 4.5. After reacting for 1 hour, 0.5 g of curing agent glutaraldehyde was added and the reaction was continued for 1 hour to obtain magnetic microcapsules.

[0169] 2. Preparation of magnetic film

[0170] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 6:4, and stirred at a speed of 1500rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AG PET film with a thickness of 0.12 using a coating machine, and the coating thickness was 0.35mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the mixed layer of water-based glue and microcapsules away from the AG PET to obtain a magnetic film.

[0171] In this embodiment, if Fig.13a The figure shows the schematic diagram of the prepared magnetic microcapsules under a microscope. Fig.13b Schematic diagram of the contrast effect of magnetic film writing made of the magnetic microcapsules is shown. Fig.13a As shown, the magnetic microcapsules have a high balling rate and are uneven in size, including three types of magnetic microcapsules with large, medium and small particle sizes. The small-sized magnetic microcapsules are aggregated and adhered to the vicinity of the large-sized magnetic microcapsules, and the overall viscosity is medium. The viscosity will have a certain impact on the average erasing speed of the magnetic film. Although this embodiment improves the mass ratio of nano-iron tetroxide and increases the blackness and contrast of the magnetic film, the mass ratio of nano-ferrite in the magnetic particles is reduced relative to that of Embodiments 1-3, the magnetic surge mobility is reduced, and the average erasing speed is medium, which is also slightly insufficient.

[0172] Comparative Example 1

[0173] The difference between this comparative example 1 and examples 1-5 is that no nano ferrite and white oil are added during the preparation process.

[0174] 1. Preparation of magnetic microcapsules

[0175] Add 2 g of nano-ferroferric oxide with an average particle size of 200 nm to 500 nm and 9 g of titanium dioxide with an average particle size of 200 nm to 500 nm in a mass ratio of 2:9 to an oily solvent of 9 g of paraffin to obtain an oil phase mixture;

[0176] After adding 0.1 wt % of a suspension stabilizer to the oil phase mixture, the oil phase mixture was dispersed in a high-speed disperser at 25° C. for 60 minutes to obtain a core material suspension;

[0177] Add 1 g of gelatin and 1 g of gum arabic to 100 g of deionized water to obtain an aqueous solution;

[0178] The core material suspension is added to the aqueous phase solution at a mass ratio of 1:10, and a stirring paddle is used to suspend and disperse at a rotation speed of 450 rpm to obtain a dispersion;

[0179] An acid-base regulator, glacial acetic acid, was added to the dispersion to adjust the pH to 4.5. After reacting for 1 hour, 1 g of curing agent, glutaraldehyde, was added and the reaction was continued for 0.5 hour to obtain magnetic microcapsules.

[0180] 2. Preparation of magnetic film

[0181] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 6:4, and stirred at a speed of 1500rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AG PET film with a thickness of 0.12 using a coating machine, and the coating thickness was 0.35mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the mixed layer of water-based glue and microcapsules away from the AG PET to obtain a magnetic film.

[0182] In Comparative Example 1, the magnetic microcapsule balling rate is high, the viscosity is high, and the magnetic surge after film formation is poor due to the lack of white oil and lipophilic nanoferrite, the erasing speed is slow (low), and the writing contrast is low. Fig.14a The figure shows the schematic diagram of the prepared magnetic microcapsules under a microscope. Fig.14b Schematic diagram of the magnetic film made using the magnetic microcapsules without surge.

[0183] Comparative Example 2

[0184] The difference between Comparative Example 2 and Examples 1-5 is that no nano-ferrosilicate is added during the preparation process.

[0185] 1. Preparation of magnetic microcapsules

[0186] Add 1 g of nano ferrite with an average particle size of 400 nm to 800 nm and 9 g of titanium dioxide with an average particle size of 200 nm to 500 nm in a mass ratio of 1:9 to an oily solvent of 1 g of white oil and 8 g of paraffin in a mass ratio of 1:8 to obtain an oil phase mixture;

[0187] After adding 1 wt % of a suspension stabilizer to the oil phase mixture, the oil phase mixture was dispersed in a high-speed disperser at 25° C. for 60 minutes to obtain a core material suspension;

[0188] Add 1 g of gelatin and 1 g of gum arabic to 100 g of deionized water to obtain an aqueous solution;

[0189] The core material suspension is added to the aqueous phase solution at a mass ratio of 1:10, and a stirring paddle is used to suspend and disperse at a rotation speed of 450 rpm to obtain a dispersion;

[0190] An acid-base regulator, glacial acetic acid, was added to the dispersion to adjust the pH to 4.5. After reacting for 0.5 hours, 1 g of curing agent glutaraldehyde was added and the reaction was continued for 0.5 hours to obtain magnetic microcapsules.

[0191] 2. Preparation of magnetic film

[0192] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 6:4, and stirred at a speed of 1500rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AG PET film with a thickness of 0.12 using a coating machine, and the coating thickness was 0.35mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the mixed layer of water-based glue and microcapsules away from the AG PET to obtain a magnetic film.

[0193] In Comparative Example 2, the magnetic microcapsule balling rate is low, the viscosity is high, and the erasing speed is medium. Since no nano-iron tetroxide is added, the writing contrast is low. Fig.15a The figure shows the schematic diagram of the prepared magnetic microcapsules under a microscope. Fig.15b Schematic diagram of the writing contrast effect of the magnetic film made using the magnetic microcapsules.

[0194] Comparative Example 3

[0195] The difference between Comparative Example 3 and Example 3 is that in the preparation of the magnetic film, the mass ratio of the magnetic microcapsules to the aqueous glue is 3:7, and the speed of the stirrer is 3000 rpm.

[0196] 1. Preparation of magnetic microcapsules

[0197] The same as Example 3, no further details are given here.

[0198] 2. Preparation of magnetic film

[0199] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 3:7, and stirred at a speed of 3000 rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AG PET film with a thickness of 0.12 using a coating machine, and the coating thickness was 0.35 mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were sequentially attached to the side of the mixed layer of water-based glue and microcapsules away from the AG PET to obtain a magnetic film.

[0200] The magnetic film obtained in this comparative example 3 is as follows Fig.16 As shown, the mixing ratio of magnetic microcapsules and water-based glue is not appropriate, and the magnetic film has obvious granularity, poor coating effect and unevenness.

[0201] Comparative Example 4

[0202] The difference between Comparative Example 4 and Example 3 is that in the preparation of the magnetic film, the mass ratio of the magnetic microcapsules to the aqueous glue is 5:5, and the speed of the stirrer is 2000 rpm.

[0203] 1. Preparation of magnetic microcapsules

[0204] The same as Example 3, no further details are given here.

[0205] 2. Preparation of magnetic film

[0206] Magnetic microcapsules and water-based glue were mixed in a mass ratio of 5:5, and stirred at a speed of 2000 rpm for 2 hours using an agitator to obtain a mixture of water-based glue and magnetic microcapsules. The mixture was coated on the surface of an AG PET film with a thickness of 0.12 using a coating machine, and the coating thickness was 0.35 mm. After drying at 100°C for 2 hours, a microcapsule coating was formed on the AG PET film. The rubber-based self-adhesive adhesive and the PET substrate were successively attached to the side of the mixed layer of water-based glue and microcapsules away from the AG PET to obtain a magnetic film.

[0207] The magnetic film obtained in this comparative example 3 is as follows Fig.17 As shown, the mixing ratio of magnetic microcapsules and water-based glue is not appropriate, and the magnetic film has obvious granularity, poor coating effect and unevenness.

[0208] In summary, the performance comparison table shown in Table 1 is obtained:

[0209] Table 1 Performance comparison table

[0210] Magnetic microcapsules / magnetic films Balling rate Viscosity Erasing speed Contrast Example 1 Higher middle high Higher Example 2 Higher Low high Higher Example 3 high Low high high Example 4 high middle middle high Example 5 high middle middle high Comparative Example 1 middle middle Low Low Comparative Example 2 Low high middle Low

[0211] Among them, the evaluation levels are divided into 5 levels: low, lower, medium, higher and high. The higher the ball formation rate, the more magnetic microcapsule spheres with uniform size are formed; the lower the viscosity and the higher the erasing speed, the faster the magnetic film erasing speed and the better the magnetic surge; the higher the contrast, the better the writing effect of the surface magnetic film.

[0212] The results show that Example 3 exhibits the best comprehensive performance in various performance indicators, with high balling rate, low viscosity, high erasing speed, and high contrast, indicating that it has obvious advantages in forming uniform magnetic microcapsule spheres, easy erasing, and writing effects, and is suitable for applications with high writing requirements. Example 1, Example 2, Example 4, and Example 5 also show good performance, with high or relatively high balling rate, low or medium viscosity, and high or high erasing speed and contrast. Although their performance indicators are not as good as Example 3, they still have a good user experience and are suitable for general application requirements. On the contrary, the comprehensive performance of Comparative Examples 1 and 2 is poor. The balling rate and viscosity of Comparative Example 1 are both medium, the erasing speed is low, and the contrast is low, indicating that its magnetic microcapsule is not uniformly formed, it is difficult to erase during use, and the writing effect is poor. The balling rate of Comparative Example 2 is low, the viscosity is high, the erasing speed is medium, and the contrast is very low. These shortcomings make them have significant limitations in practical applications, and it is necessary to further improve the material ratio and process parameters to improve their comprehensive performance.

[0213] In terms of material selection, magnetic materials such as nano-ferrite and ferroferric oxide, nano-titanium dioxide, suspension stabilizers and other non-magnetic materials play a key role. By rationally selecting the ratio and preparation process of these magnetic materials, the performance of magnetic microcapsules and magnetic films can be significantly improved.

[0214] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0215] It should also be noted that the exemplary embodiments mentioned in the present invention describe some methods or systems based on a series of steps or devices. However, the present invention is not limited to the order of the above steps, that is, the steps can be performed in the order mentioned in the embodiments, or in a different order from the embodiments, or several steps can be performed simultaneously.

[0216] The above is only a specific implementation of the present invention. Those skilled in the art can clearly understand that for the convenience and simplicity of description, the specific working processes of the systems, modules and units described above can refer to the corresponding processes in the aforementioned method embodiments, and will not be repeated here. It should be understood that the protection scope of the present invention is not limited to this. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be covered within the protection scope of the present invention.

Claims

1. A magnetic microcapsule for preventing particle sedimentation, characterized in that: The magnetic microcapsule comprises a wall material and a core material, wherein the wall material is a mixture of anionic polymers and cationic polymers, and the core material is a mixture of magnetic particles, non-magnetic particles, an oily solvent and a suspension stabilizer; the suspension stabilizer comprises any one or more of phthalate, polyamide wax, polysiloxane, sorbitan oleate, sorbitan monostearate, silicon dioxide, aluminum magnesium silicate and lithium magnesium silicate; wherein the cationic polymer comprises one or two of gelatin and ε-polylysine, and the anionic polymer comprises carboxylic acid One or more of sodium methyl cellulose, gum arabic, and sodium alginate; the magnetic particles include nano-ferroferric oxide, and also include one or two of lipophilic nano-ferrite and nano-NdFeB, wherein the magnetic strengths of the nano-ferroferric oxide, the nano-ferrite and the nano-NdFeB are different; the non-magnetic particles are lipophilic nano-titanium dioxide; the nano-ferrite in the magnetic particles includes one or more of nano-manganese-zinc ferrite, nano-nickel-zinc ferrite, nano-magnesium-manganese ferrite, and nano-aluminum-manganese ferrite.

2. The magnetic microcapsule according to claim 1, characterized in that The cationic polymer and the anionic polymer in the wall material are gelatin and gum arabic respectively; the core material comprises nano-ferroferric oxide, the nano-ferrite and the nano-titanium dioxide; the oily solvent comprises white oil and paraffin; the suspension stabilizer comprises any one or more of phthalic acid ester, polyamide wax, polysiloxane, sorbitan oleate, sorbitan monostearate, silicon dioxide, magnesium aluminum silicate and magnesium lithium silicate.

3. The magnetic microcapsule according to claim 1, characterized in that The cationic polymer and the anionic polymer in the wall material are ε-polylysine and gum arabic respectively, the core material comprises nano-ferroferric tetroxide, the nano-ferrite and the nano-titanium dioxide, and the oily solvent comprises white oil and paraffin.

4. The magnetic microcapsule according to claim 2, characterized in that The mass ratio of the gelatin to the gum arabic is 1:0.8-1.2; the mass ratio of the nano-ferroferric oxide, the nano-ferrite and the nano-titanium dioxide is 1:1.5-3:9; and the mass ratio of the white oil to the paraffin is 1:7-9.

5. The magnetic microcapsule according to claim 1, characterized in that The suspension stabilizer is a mixture of polyamide wax and sorbitan oleate, or a mixture of phthalate and polyamide wax, or a mixture of polysiloxane and silicon dioxide.

6. A method for preparing magnetic microcapsules that prevent particle sedimentation, used for preparing the magnetic microcapsules according to any one of claims 1 to 5, characterized in that: The following steps are involved: adding magnetic particles and non-magnetic particles to an oily solvent in a predetermined mass ratio to obtain an oil phase mixture; Adding 0.1-2 wt% of a suspension stabilizer to the oil phase mixture and dispersing the mixture in a high-speed disperser at room temperature for 60-90 minutes to obtain a core material suspension; Adding the cationic polymer and the anionic polymer into deionized water according to a preset mass ratio to obtain an aqueous phase solution; Adding the core material suspension into the aqueous phase solution, and dispersing the core material suspension by stirring to obtain a dispersion; An acid-base regulator is added to the dispersion to adjust the pH to a preset value. After reacting for a first preset time, a curing agent is added and the reaction is continued for a second preset time to obtain magnetic microcapsules.

7. The method for preparing magnetic microcapsules for preventing particle sedimentation according to claim 6, characterized in that: The magnetic particles include nano-iron tetroxide, and the magnetic particles also include one or both of nano-ferrite and nano-NdFeB; The step of adding the magnetic particles and the non-magnetic particles to the oily solvent in a predetermined mass ratio to obtain an oil phase mixture comprises: Nano ferrite, nano ferroferric oxide and nano titanium dioxide are added into an oily solvent in a mass ratio of 1:1.5 to 3:9 to obtain an oil phase mixture, wherein the oily solvent comprises white oil and paraffin in a mass ratio of 1:7 to 9.

8. The method for preparing magnetic microcapsules for preventing particle sedimentation according to claim 6, characterized in that: The core material suspension is obtained by adding 0.1-2 wt% of a suspension stabilizer to the oil phase mixture and dispersing the mixture in a high-speed disperser at room temperature for 60-90 minutes to obtain the core material suspension. First, add 0.5-0.8 wt% of a mixture of polyamide wax and sorbitan oleate to the oil phase mixture, and disperse it in a high-speed disperser at a speed of 1800-2000 rpm for 20-30 minutes at room temperature; Add 0.4-0.8 wt% of a mixture of phthalate and polysiloxane, and continue to disperse at a speed of 1200-1500 rpm for 20-30 minutes at room temperature; 0.1-0.4 wt% of silicon dioxide is added, and the mixture is dispersed at a speed of 1000-1200 rpm for 20-30 minutes at room temperature to obtain the core material suspension.

9. The method for preparing magnetic microcapsules for preventing particle sedimentation according to claim 6, characterized in that: The step of adding the cationic polymer and the anionic polymer into deionized water at a preset mass ratio to obtain an aqueous solution comprises: adding gelatin and gum arabic into deionized water at a mass ratio of 1:0.8 to 1.2 to obtain an aqueous solution; The step of adding the core material suspension to the aqueous solution and dispersing the core material suspension by stirring to obtain a dispersion comprises: adding the core material suspension to the aqueous solution at a ratio of 1:7 to 10, and using a stirring paddle to suspend and disperse at a rotation speed of 200 to 800 rpm to obtain the dispersion; The step of adding an acid-base regulator to the dispersion to adjust the pH to a preset value, reacting for a first preset time, adding a curing agent, and continuing the reaction for a second preset time to obtain the magnetic microcapsules comprises: adding glacial acetic acid as an acid-base regulator to the dispersion to adjust the pH to 4.4-4.5, reacting for 0.5-1 hour, adding glutaraldehyde as a curing agent, and continuing the reaction for 0.5-1 hour to obtain the magnetic microcapsules.

10. A magnetic film, characterized in that: The magnetic film includes a PET substrate layer, a rubber-based self-adhesive layer located on the PET substrate layer, a water-based glue and magnetic microcapsule mixed layer located on the rubber-based self-adhesive layer, and an AG PET film layer on the water-based glue and magnetic microcapsule layer; the thickness of the AG PET film is 0.1 to 0.14 mm; the water-based glue includes any one or more of a PVA aqueous solution, a polyurethane, an ultraviolet absorber, and a leveling agent, wherein the magnetic microcapsule is a magnetic microcapsule as described in any one of claims 1 to 5 or a magnetic microcapsule prepared by the preparation method described in any one of claims 6 to 9.

Citation Information

Cited By

  • Ultraviolet light absorber and preparation method thereof

    CN120248679A

  • Magnetic microcapsule, preparation method thereof and magnetophoresis display handwriting board

    CN120900530A